Teaching to exceed the English language arts common core state standards a critical inquiry approach for 6-12 classrooms - Beach, Richard; Haertling-Thein, Amanda; Webb, Allen (New York Routledge, 2016)
Timely, thoughtful, and comprehensive, this text directly supports pre-service and in-service teachers in developing curriculum and instruction that both addresses and exceeds the requirements of the Common Core State Standards. Adopting a critical inquiry approach, it demonstrates how the Standards' highest and best intentions for student success can be implemented from a critical, culturally relevant perspective firmly grounded in current literacy learning theory and research. It provides specific examples of teachers using the critical inquiry curriculum framework of identifying problems and issues, adopting alternative perspectives, and entertaining change in their classrooms to illustrate how the Standards can not only be addressed but also surpassed through engaging instruction.
Table of contents : Preface -- Section I. Theoretical frameworks/foundations of English language arts instruction -- Section II. Implementing and exceeding the common core state standards -- Section III. Evaluation, assessment, and reflection -- References -- Index
Includes bibliographical references and index.
Keywords: Language arts (Secondary) -- Curricula -- United States -- States; Language arts (Secondary) -- Standards -- United States -- States